Sensorless control of PMSM with fuzzy model reference adaptive system - M’hamed, Larbi; Roufaida, Adjir; nawal, ait ameur mezyane (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
To improve the performance of permanent-magnet synchronous motor (PMSM) drives powered by the voltage inverter with PWM control, a sensorless control scheme based on a Model Reference Adaptive System (MRAS) a fuzzy logic controller (FLC) based in with fuzzy supervisor structure. The major drawbacks of the conventional MRAS, namely chattering phenomena, high-order harmonics andexternal noise, are discussed. These drawbacks affect the estimated speed accuracy of the MRAS and reduce the control reliability of the system. To eliminate these drawbacks, an FLC is designed and integrated into the MRAS to adjust the observer gain to reduce the chattering in closed loop speed and closed loop current/torque. Comparative simulations using the proposed Fuzzy-MRAS and the conventional MRAS are performed to validate the effectiveness of the proposed FLC structure. Performance simulations of the overall proposed Fuzzy-MRAS based sensorless control scheme are performed to verify the robustness and control reliability of the system. The results show that the proposed Fuzzy MRAS has satisfactory performances with reduction of total harmonic distortion generated in the phase currents.